Changes of the paradigm of publications search and use by researchers - V. N. Gureev; N. A. Mazov (Библиосфера, 2016)
The article reviews the most significant changes in searching models and using patterns of readers while working with scientific literature. A shift in the search paradigm and reading models is caused by both common trends of science and technology development, and specific changes in librarianship. Furthermore, an inverse relation is also true, when knowledge on readers’ behavior can be effectively used in acquisition modeling, in providing researchers with scientific information, in revising networks of library access, as well as in improving the editorial policy of academic journals.